2019
DOI: 10.1080/02671522.2019.1568534
|View full text |Cite
|
Sign up to set email alerts
|

“A freak that no one can love”: difficult knowledge in testimonials on school bullying

Abstract: This study adopts a testimonial approach to bullying victimisation, and aims to create a deeper understanding of the experiences and effects of being a bullying target. Four written narratives about being subjected to school bullying were analysed according to interpretative phenomenological analysis. From the analysis, four themes were constructed, which represented different elements of victimhood: (1) Self-blame in which victims view themselves as the cause of the bullying, (2) Abandonment in which victims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…With time, they began to see their own actions as accountable for the bullying and started to suspect that they might be at some fault, so causal attribution gravitated toward internal attribution. Self-blame among victims of school bullying has also been found in other studies ( Tholander et al, 2020 ; Thornberg et al, 2013 ; Viala, 2014 ), and might, at least partly, be a result of internalizing the negative image of them as deviant and not fitting in that is repeatedly produced in bullying behaviors and conversations directed toward them ( Thornberg et al, 2013 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…With time, they began to see their own actions as accountable for the bullying and started to suspect that they might be at some fault, so causal attribution gravitated toward internal attribution. Self-blame among victims of school bullying has also been found in other studies ( Tholander et al, 2020 ; Thornberg et al, 2013 ; Viala, 2014 ), and might, at least partly, be a result of internalizing the negative image of them as deviant and not fitting in that is repeatedly produced in bullying behaviors and conversations directed toward them ( Thornberg et al, 2013 ).…”
Section: Discussionsupporting
confidence: 67%
“…Bullying has mainly been studied through surveys measuring prevalence, impact on mental health, and protective factors ( Bjereld et al, 2015 ). However, studies that have explored the victims’ own perceptions and interpretation of their victimization path ( Bjereld, 2016 ; Carlisle & Rofes, 2007 ; DeLara, 2006 , 2008 ; Tholander, 2019 ; Tholander et al, 2020 ; Thornberg et al, 2013 ; Thornberg, 2015 ; Wójcik & Flak, 2019 ) are still scarce. Considering the current body of research on school bullying, there is a need to conduct qualitative studies to gain an understanding of former victims’ perspectives and interpretation of their bullying experience.…”
Section: Current Studymentioning
confidence: 99%
“…This was succinctly put by one student who stated that they were bullied, 'Because I am me.' While this statement might indicate self-blame (Chen and Chen 2019;Tholander, Lindberg, and Svensson 2020), it nonetheless alludes to how those who are subjected to bullying might be subjected to it because of their perceived difference and their perceived inability or unwillingness to fit in (Thornberg 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been relatively few studies focussing on students' understandings of their own bullying experiences, these have also suggested that victims of bullying might view themselves as a reason for the bullying (e.g. Wong, Cheng, and Chen 2013;Side and Johnson 2014;Gardella et al 2020), that they sometimes internalise the expressions and views of those doing the bullying and position themselves in similarly negative ways (Thornberg et al 2013), and that they articulate selfblame (Tenenbaum et al 2011;Chen and Chen 2019;Tholander, Lindberg, and Svensson 2020). A recent study of students' perceptions of why they were bullied pointed to the importance of relational dynamics, physical characteristics and non-physical personal characeristics (Gardella et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Former victims have described how they experienced lack of support from teachers and other professionals, leading to feelings of abandonment during the period when they had been bullied (Tholander, Lindberg, and Svensson 2019).…”
Section: Introductionmentioning
confidence: 99%